2023
DOI: 10.3390/polym15163419
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of 3D Printing Parameters for Enhanced Surface Quality and Wear Resistance

Abstract: In recent years, there has been a growing interest in the field of 3D printing technology. Among the various technologies available, fused deposition modeling (FDM) has emerged as the most popular and widely used method. However, achieving optimal results with FDM presents a significant challenge due to the selection of appropriate process parameters. Therefore, the objective of this research was to investigate the impact of process parameters on the tribological and frictional behavior of acrylonitrile butadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…A fill of 100% should enable it not to penetrate the inner layers of the structure and, despite the higher material consumption, increase the strength of the fabricated parts. The linear infill pattern allows the material to be applied in parallel lines, which should lead to a higher tensile strength along the infill axis [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A fill of 100% should enable it not to penetrate the inner layers of the structure and, despite the higher material consumption, increase the strength of the fabricated parts. The linear infill pattern allows the material to be applied in parallel lines, which should lead to a higher tensile strength along the infill axis [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…There are also articles in which cyclic tests were used to evaluate the strength. Articles [ 21 , 22 ] focused on PLA material and its modified counterpart, where it was shown that, under the same loading conditions, the fatigue life of the 3D-printed samples was similar. Additionally, the presence of porosity in the material was demonstrated by conducting SEM (scanning electron microscope) analyses [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each protocol serves to improve the overall finish, mechanical integrity, and cleanliness of the printed objects, ensuring they meet the required standards for various applications, while also potentially reducing the presence of defects that could compromise their functionality and longevity [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…The printing parameters affecting the mechanical properties and production cost of 3D-printed samples are the layer thickness (0.10 mm/0.15 mm/0.20 mm) and infill percentage (50%/75%/100%). The mechanical properties investigated were previously determined by the authors of the present work, namely tensile strength [ 6 , 9 , 28 ], compression strength [ 8 ], flexural strength [ 7 , 9 ], impact strength [ 29 ], and hardness [ 28 , 30 ].…”
Section: Methodsmentioning
confidence: 99%